Generation of combined hepatocellular‐cholangiocarcinoma through transdifferentiation and dedifferentiation in p53‐knockout mice. Issue 8 (27th June 2021) - Liu, Yang; Xin, Bing; Yamamoto, Masahiro; Goto, Masanori; Ooshio, Takako; Kamikokura, Yuki; Tanaka, Hiroki; Meng, Lingtong; Okada, Yoko; Mizukami, Yusuke; Nishikawa, Yuji
Abstract: The two principal histological types of primary liver cancers, hepatocellular carcinoma (HCC) and cholangiocarcinoma, can coexist within a tumor, comprising combined hepatocellular‐cholangiocarcinoma (cHCC‐CCA). Although the possible involvement of liver stem/progenitor cells has been proposed for the pathogenesis of cHCC‐CCA, the cells might originate from transformed hepatocytes that undergo ductular transdifferentiation or dedifferentiation. We previously demonstrated that concomitant introduction of mutant HRAS V12 (HRAS) and Myc into mouse hepatocytes induced dedifferentiated tumors that expressed fetal/neonatal liver genes and proteins. Here, we examine whether the phenotype of HRAS‐ or HRAS/Myc‐induced tumors might be affected by the disruption of the Trp53 gene, which has been shown to induce biliary differentiation in mouse liver tumors. Hepatocyte‐derived liver tumors were induced in heterozygous and homozygous p53‐knockout (KO) mice by hydrodynamic tail vein injection of HRAS‐ or Myc‐containing transposon cassette plasmids, which were modified by deleting loxP sites, with a transposase‐expressing plasmid. The HRAS‐induced and HRAS/Myc‐induced tumors in the wild‐type mice demonstrated histological features of HCC, whereas the phenotype of the tumors generated in the p53‐KO mice was consistent with cHCC‐CCA. The expression of fetal/neonatal liver proteins, including delta‐like 1, was detected in the HRAS/Myc‐induced but not in the HRAS‐induced cHCC‐CCA tissues. The dedifferentiation in the HRAS/Myc‐induced tumors was more marked in the homozygous p53‐KO mice than in the heterozygous p53‐KO mice and was associated with activation of Myc and YAP and suppression of ERK phosphorylation. Our results suggest that the loss of p53 promotes ductular differentiation of hepatocyte‐derived tumor cells through either transdifferentiation or Myc‐mediated dedifferentiation. Abstract : The loss of p53 promotes ductular differentiation of hepatocyte‐derived tumor cells through either transdifferentiation or Myc‐mediated dedifferentiation. This figure shows a two‐dimensional perspective of the hepatocyte‐derived tumors with respect to transdifferentiation and dedifferentiation.